146k views
3 votes
Which expressions is equivalent to 3x (2x– 3)?

(hint: select ALL that apply. Remember to distribute!)

Which expressions is equivalent to 3x (2x– 3)? (hint: select ALL that apply. Remember-example-1
User Yvon
by
4.9k points

2 Answers

2 votes


3x(2x - 3) = 3x2x - 3x3 \\ = 6 {x}^(2) - 9x \\ thank \: you

User James Ikubi
by
4.7k points
5 votes

Hi ;-)


3x(2x-3)=3x\cdot2x-3x\cdot3=\\\\=\boxed{6x^2-9x}=\boxed{-9x+6x^2}

User Bhavani Ravi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.